Bioefficacy of controlled release formulations of diuron on Brassica rapa - Mazlan, Norida; Omar, Dzolkhifli; Mohamad, R. B. (Universiti Putra Malaysia Press, 2012)
Controlled-release formulations (CRF) of diuron were prepared in laboratory using the concept of physical matrix utilizing sodium alginate and kaolin. The release rates of diuron from the formulations were determined by chemical assay its efficacy on plant was tested on Brassica rapa. In the chemical assay using high performance chromatography with UV detector, significant differences in the release rate between formulations were observed from 3 to 7 days after the granules had been placed in distilled water. The formulation having a 1:1 ratio of alginate to kaolin with 1mm granule size showed the fastest release of diuron, while release from the 2mm granules was slower. Increasing the proportion of kaolin to sodium alginate in the CRF reduced the release rate of active agent. The bioefficacy using Brassica rapa as a bioindicator showed that CRF released slower than the conventional formulation at the beginning of the treatments. In the 3rd week after the treatment (WAT), there was no significant difference in the mortality as compared to the conventional formulation at 16 WAT. The same results were also observed up to 24 WAT, the CRF caused between 40-70% mortality, while the conventional formulation treatment caused only 6% mortality. Among the CRF, the AK-2 with 1:1 ration of alginate:kaolin was found to have given the best result with the highest percentage mortality of the seedlings.